Integrated teaching enabling the approach of living value and skills - Pham, Xuan Thanh (Journal of Technical Education Science, 2016)
It requires vocational education not only specialize in professional competence, but also approach the profession value and characteristic. However, the fact from the actual survey of the subject named “Assessment of integrated lectures do not concentrate on forming the attitude, manner as well as living value and skills to students for their future occupation. The above issue has been existed since 2009 up to now. Is it for the limitation of accessing the theory of integrated teaching in our country? This article introduces and chooses transformative learning theory as the basic solution for the above mentioned issue from which the model and framework for integrated teaching are proposed so that the living value and skills for student are enhanced